Clinical and economic impacts of large volume delayed sampling and pathogen reduction technology platelet processing strategies in the United States. Issue 10 (21st July 2021) - Earnshaw, Stephanie; Beyhaghi, Hadi; McDade, Cheryl; Purser, Molly; Marriott, Robert; Daane, Lori; Le Coent, Virginie; Yang, Julie; Toback, Seth
Abstract: Background: Large volume delayed sampling (LVDS) and pathogen reduction technology (PRT) are strategies for platelet processing to minimize transfusion of contaminated platelet components (PCs). This study holistically compares the economic and clinical impact of LVDS and PRT in the United States. Study Design and Methods: A decision model was constructed to simulate collection, processing, and use of PCs and to compare processing strategies: PRT with 5‐day shelf life, LVDS with 7‐day shelf life (LVDS7), and LVDS with 5‐day shelf life extended to 7 days with secondary testing (LVDS5/2). Target population was adults requiring two or more transfusions. Collection, processing, storage, and distribution data were obtained from the National Blood Collection and Utilization Survey and published literature. Patient outcomes associated with transfusions were obtained from AABB guidelines, meta‐analyses, and other published clinical studies. Costs were obtained from reimbursement schedules and other published sources. Results: Given 10, 000 donated units, 9512, 9511, and 9651 units of PRT, LVDS5/2, and LVDS7 PCs were available for transfusion, respectively. With these units, 1502, 2172, and 2329 transfusions can be performed with similar levels of adverse events. Assuming 30 transfusions a day, a hospital would require 69, 325, 47, 940, and 45, 383 units of PRT, LVDS5/2, and LVDS7 platelets to perform these transfusions. The mean costs to perform transfusions were significantly higher with PRT units. Conclusions: Compared with PRT, LVDS strategies were associated with lower costs and higher PC availability while patients experienced similar levels of adverse events. Increased utilization of LVDS has the potential to improve efficiency, expand patient access to platelets, and reduce health care costs.